2021
DOI: 10.1090/mcom/3636
|View full text |Cite
|
Sign up to set email alerts
|

Totally positive algebraic integers with small trace

Abstract: The “Schur-Siegel-Smyth trace problem” is a famous open problem that has existed for nearly 100 years. To study this problem with the known methods, we need to find all totally positive algebraic integers with small trace. In this work, on the basis of the classical algorithm, we construct a new type of explicit auxiliary functions related to Chebyshev polynomials to give better bounds for S k S_k , and reduce sharply the computing time. We are then able to push the computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Even stronger bounds than (1.14) can be obtained by the method of auxiliary polynomials introduced by Smyth [9], once we observe that the potential energy is the trace of the polynomial with roots (x i − x j ) 2 . The best constant in the trace problem has been obtained with Smyth's method and is 1.793145, due to Wang-Wu-Wu [10].…”
Section: Note Also Thatmentioning
confidence: 99%
See 1 more Smart Citation
“…Even stronger bounds than (1.14) can be obtained by the method of auxiliary polynomials introduced by Smyth [9], once we observe that the potential energy is the trace of the polynomial with roots (x i − x j ) 2 . The best constant in the trace problem has been obtained with Smyth's method and is 1.793145, due to Wang-Wu-Wu [10].…”
Section: Note Also Thatmentioning
confidence: 99%
“…Their results have applications to what is nowadays called the Schur-Siegel-Smyth trace problem (see e.g. [1] for an overview of the problem and [8,10] for the current state of the art).…”
Section: Introductionmentioning
confidence: 99%
“…In his letter to Smyth dated 24 February 1998, Serre showed that, for any t > 0 and γ ∈ [0, 1], the inequality However, we know that this measure is not perfectly optimized for the trace problem. Indeed, the 14 totally positive algebraic integers α with tr(α)/ deg(α) at most 1.793 have all conjugates lying in the support of µ [22], while the support of an optimal measure would contain none of these points by Proposition 5.8.…”
Section: Limits Of Measures and Balayagementioning
confidence: 99%
“…It has long been known that there are infinitely many totally positive algebraic integers α with tr(α)/ deg(α) at most 2, with Siegel citing the family (1.1) 4 cos 2 (π/p) : p an odd prime as an example [17]. At the other end, the totally positive algebraic integers satisfying tr(α) < 1.793145 • deg(α) have been determined explictly; there are a total of 14 such algebraic integers [22]. This last result fits into the framework of the following problem, which was codified by Borwein in [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation